1984
DOI: 10.1038/309126a0
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-3 supports growth of mouse pre-B-cell clones in vitro

Abstract: Study of the differentiation of immunoglobulin-producing B lymphocytes has been hampered by the inability to maintain homogeneous populations of precursor cells in vitro. We describe here that interleukin-3 supports the growth of freshly isolated fetal liver pre-B cells and the long-term culture of interleukin-3 dependent pre-B-cell clones that can be induced to mature into antibody secreting cells in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(88 citation statements)
references
References 33 publications
1
86
0
1
Order By: Relevance
“…Although the precise role of IL-3 in the early stages of B lymphopoiesis is unknown, the growth factor was required to isolate clonal pro-B and pre-B cell lines (5,21,25,26), and the IL-3 gene is activated in some cases of human acute pro-B cell leukemia associated with the t(5;14) chromosomal translocation (27,28). The apparent leukemogenic effects of IL-3 activation in man strongly suggest that the cytokine mediates cell growth and survival in at least a subset of early B cell progenitors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise role of IL-3 in the early stages of B lymphopoiesis is unknown, the growth factor was required to isolate clonal pro-B and pre-B cell lines (5,21,25,26), and the IL-3 gene is activated in some cases of human acute pro-B cell leukemia associated with the t(5;14) chromosomal translocation (27,28). The apparent leukemogenic effects of IL-3 activation in man strongly suggest that the cytokine mediates cell growth and survival in at least a subset of early B cell progenitors.…”
Section: Resultsmentioning
confidence: 99%
“…This process is greatly influenced by cytokines that act on lymphoid and hematopoietic precursors, including interleukin 3 (IL-3), which supports the in vitro proliferation of multipotent stem cells as well as many progenitor cells already committed to particular lineages (4). When IL-3-dependent cell lines are deprived of growth factor, they not only stop proliferating but undergo apoptosis as well, indicating that IL-3 promotes cell survival by suppression of programmed cell death (5)(6)(7). Thus, it is important to identify the key molecules through which IL-3-generated survival signals are transduced.…”
mentioning
confidence: 99%
“…Ba/F3 is a murine pro B-cell line established from mouse fetal liver. 18 The cell line grows in suspension (Roswell Park Memorial Institute 1640 medium with 10% fetal bovine serum, 2 mM L-glutamine, MO] and is kept in a cell culture flask at 37°C in 5% carbon dioxide atmosphere. As for the THP-1 cells, they are human monocytic cells derived from a 1-year-old boy with acute monocytic leukemia.…”
Section: Materials and Methods Gd 2 O 3 Nanoparticlesmentioning
confidence: 99%
“…This inhibitory effect of IL-3 was very surprising to us since stimulatory roles of IL-3 in B cell development have been reported. For example, several investigators have established IL-3-dependent B220 + pre-B cell lines [29,30] and pro-B cell lines [31][32][33]. It was recently reported that IL-3 can support the proliferation of B220 + c-kit + pre-B cells in the presence of stromal cells [34].…”
Section: Cytokine Regulation Of Lymphohematopoietic Progenitorsmentioning
confidence: 99%